Effects of forest roads on Ips sexdentatus infestation in black pine forest - Gonca Ece Özcan; Korhan Enez; Burak Arıcak (Turkish Science and Technology Publishing (TURSTEP), 2018)
Forest roads are important transportation equipment through forested areas in the rugged, mountainous terrain of northern Turkey. Forest roads harm forest ecosystems due to both the manner in which they are established and how they are used afterwards. Damage to trees that occur during road construction through forests stresses trees, which facilitates outbreaks of bark beetle populations. Bark beetles are significant risk to the health and productivity of Turkish pine forests and to pine forests worldwide. In particular, Ips sexdentatus (Boerner) (Coleoptera, Curculionidae, Scolytinae) is a particularly destructive species of bark beetle in Turkish forests. Their damage to coniferous trees threatens the sustainability of the forest ecosystems. This study primarily aims to assess the intensity of damage that I. sexdentatus inflicts on Pinus nigra J.F.Arnold stands relative to several parameters: the distance to the nearest forest road, aspect (shady - sunny), slope (0–15% or >15%), and other stand characteristics. In this study, we show how damage by an I. sexdentatus infestation in pure black pine stands varies with distance to forest roads and in situ edaphic factors. We sampled 45 plots (400 m2 each), slope, aspect and distances to the nearest forest road was determined using ArcGIS software and the region‘s road network overlays. Results showed that trees located within 100 m from the nearest forest road were the most severely damaged ones. The intensity of I. sexdentatus damage was about 16% in a hectare. Trees that were in 16–20 cm diameter class were damaged more often. I. sexdentatus damage did not show any significant correlation with the slope, aspect or degree of canopy closure.
Keywords: Bark beetle; S; Ips sexdentatus; Agriculture (General); forest road network; Agriculture; damage; ArcGIS; S1-972; 15. Life on land